An information based approach to stochastic control problems - Bania, Piotr (Zielona Góra: Uniwersytet Zielonogórski)
An information based method for solving stochastic control problems with partial observation is proposed. First, information-theoretic lower bounds of the cost function are analysed. It is shown, under rather weak assumptions, that reduction in the expected cost with closed-loop control compared with the best open-loop strategy is upper bounded by a non-decreasing function of mutual information between control variables and the state trajectory. On the basis of this result, an "information based control" (IBC) method is developed.
Keywords: stochastic control; feedback; information; entropy